Evaluation of the physiological effect of Saccharomyces boulardii a candidate for the manufacture of probiotics isolated from Garcina mangostana fruit pericarps - Odette N Kabena; Julia N Diakese; Jean Jacques D Amogu; Ruth M Katunda; Lionel S Asamboa; Gracias I Mbokolo; Francis K Tshiswaka; Didier L Dianzuangani (International Journal of Agricultural Research, Innovation and Technology, 2026)
This study aimed to isolate the Saccharomyces boulardii strain from Garcinia mangostana fruit from Kinshasa; to determine its thermoresistance; and finally, to determine its antagonistic effect towards Lactobacillus vaginalis and Staphylococcus aureus to determine its suitability for use as a probiotic. The results of this study show that Sacharomyces boulardii isolated from Garcinia mangostana fruit from Kinshasa is tolerant at 44°C and resistant only at 60 and 75°C. Sacharomyces boulardii isolated from Garcinia mangostana fruit in Kinshasa has no antagonistic effect on Lactobaccilus vaginalis and Staphylococcus aureus, so it lives in perfect synergy. Saccharomyces boulardii isolated from the fruit of Garcinia mangostana in Kinshasa could be a good candidate that may well contribute to the restoration of vaginal microbiota than other marketed strains. We therefore suggest that further studies on other probiotic selection criteria be carried out on the isolated strain, with a view to the scientific validation of our results. Int. J. Agril. Res. Innov. Tech. 15(2): 165-170, Dec 2025